Algorithm improvement to predict fault location of simultaneous fault in underground cable - Apisit, Chaowat; Ngaopitakkul, Atthapol (My University, 2013)
In the literature for fault location, most of research works have never been mentioned about effects of simultaneous faults. This paper presents a new decision algorithm that will be developed in order to predict precisely fault location, during simultaneous fault, in an underground distribution system using discrete wavelet transform (DWT). The advantage of the DWT is that the band of analysis can be fine adjusted so that high frequency components and low frequency components are detected precisely, consequently DWT is considered herein. The fault signal is simulated using ATP/EMTP. The DWT is used to detect the high frequency components. Coefficients of positive sequence current signals are calculated. The positive sequence current as extracted to several scales with the DWT, and the coefficients of the first scale from the DWT are investigated. The time that the fault signal uses to reach the ends of the distribution line is considered, then, applied so that the distance of fault can be calculated. Various case studies have been carried out including the single fault and simultaneous fault. The result is found that the proposed algorithm gives satisfactory both in case of single fault and simultaneous fault. © 2013 The Institute of Electrical Engineers of Japan.
Keywords: Discrete wavelet transforms; Fault location; Simultaneous fault; Travelling wave